Cardioneuroablation in the treatment of neurocardiogenic syncope and functional bradyarrhythmias. A literature review - M. V. Gorev; F. G. Rzaev; A. D. Vakhrushev; E. N. Mikhailov (Российский кардиологический журнал, 2025)
Interest in the autonomic regulation of the cardiovascular system does not wane. Changes in autonomic nervous system activity are involved in the pathogenesis of acute and chronic conditions, such as sinus bradycardia, sinus arrest and atrioventricular block, vasovagal syncope and other types of syncopal conditions. Traditional methods of prevention and treatment of such conditions include lifestyle changes, pharmacotherapy and, in some cases, pacemaker implantation, but in many cases they are unable to eliminate the symptoms or cure the disease. We conducted a descriptive review of the most significant publications on effectiveness and development of the cardiac neuroablation technique in patients with vasovagal syncope and neurogenic functional bradyarrhythmias — sinus node dysfunction and atrioventricular conduction disorders. This technique allows to effectively prevent neurocardiogenic syncope relapses, reduce the tendency to functional bradyarrhythmias by eliminating pathological parasympathetic tone. Cardioneuroablation allows to eliminate indications for pacemaker implantation or to delay its implementation.